Ethical and legal issues in haematopoietic stem cells (HSC) donation: the controversial and problematic aspects in minors - Delbon, Paola; Attico, Federica; De Nadai, Matteo; Almici, Camillo; Ferrari, Emilio; Malagola, Michele; Conti, Adelaide (Acta Biomedica Atenei Parmensis, 2024)
Starting from the case of a male adult patient suffering from Acute Myeloid Leukaemia for whom no HLA-compatible non-family donors were found, and for whom his adolescent daughter was then proposed as a donor, this article deals with the delicate issue of the minor’s consent, especially when the minor’s legal representative is in conflict of interest. In the case presented above as an example, this conflict arose when the parent was simultaneously the legal representative of the donor and the transplant recipient. The Authors report ethical and legal issues in the collection of haematopoietic stem cells from minors for the purpose of family donation and analyse the guidelines from some overseas scientific societies, the conventions drawn up within international organisations and the Italian legal system. Such a donation raises complex questions, with regard to the admissibility of the procedure, the ownership of the decision-making power and the criteria of the decision-making process: this process must take place in a context that guarantees the protection of the potential donor and his or her autonomy.